ECLAS Lifetime Achievement Award to Prof. Imre jámbor and Prof. Richard Stiles - Szilágyi, Kinga (4D Journal of Landscape Architecture and Garden Art, 2013)
ECLAS Lifetime Achievement Award to Prof. Imre jámbor and Prof. Richard Stiles
Keywords: lifetime achievement; ECLASű